1989
DOI: 10.1095/biolreprod41.3.414
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transplantation in Early Pig Embryos1

Abstract: Nuclear transfer was evaluated in early porcine embryos. Pronuclear stage embryos were centrifuged, treated with cytoskeletal inhibitors, and subsequently enucleated. Pronuclei containing karyoplasts were placed in the perivitelline space of the enucleated zygote and fused to the enucleated zygote with electrofusion. The resulting pronuclear exchange embryos were either monitored for cleavage in vitro (9/13 cleaved and contained 2 nuclei after 24 h, 69%) or for in vivo development. In vivo development after 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
138
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(143 citation statements)
references
References 31 publications
1
138
0
4
Order By: Relevance
“…All clones were derived by nuclear transplantation using nuclei from blastomeres as donors (Willadsen, 1986;Prather et al, 1987Prather et al, , 1989. Importantly, these researchers used oocytes rather than zygotes as recipients.…”
Section: Mammalian Nuclear Transfer: Selected Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…All clones were derived by nuclear transplantation using nuclei from blastomeres as donors (Willadsen, 1986;Prather et al, 1987Prather et al, , 1989. Importantly, these researchers used oocytes rather than zygotes as recipients.…”
Section: Mammalian Nuclear Transfer: Selected Highlightsmentioning
confidence: 99%
“…For normal development to proceed, it is crucial that, in a Briggs et al, 1952Briggs et al, 1962 Nuclear transfer-derived frogs Gurdon, 1962Gurdon, 1975 Rabbit nuclear transfer Bromhall, 1975Bromhall, 1979 Nuclear transplantation in fish Gasaryan et al, 1979Gasaryan et al, 1981 Derivation of mouse ES cells Evans and Kaufman, 1981;Martin, 1981Martin, 1983 Nuclear transplantation in the mouse Solter, 1983 1986 Lambs cloned from blastomeres Willadsen, 1986Willadsen, 1987 Cattle cloned from blastomeres Prather et al, 1987Prather et al, 1989 Pigs cloned from blastomeres Prather et al, 1989Prather et al, 1994 Calves cloned from ICM cells First, 1994 1996 Sheep cloned from embryonic cell line Campbell et al, 1996 First mammal cloned from adult cell (sheep "Dolly") Wilmut et al, 1997Wilmut et al, 1998 Derivation of human ES cells Thomson et al, 1998Thomson et al, 2000 Mouse nuclear transfer-derived ES cells Munsie et al, 2000Munsie et al, 2002 Terminally differentiated cells cloned Hochedlinger et al, 2002aHochedlinger et al, 2002 First therapeutic application in mice Rideout et al, 2002 a ES, embryonic stem; ICM, inner cell mass. This table summarizes a number of selected highlights starting from the first demonstration of the NT technique by Briggs and King to the first "proof of principle" study in mice showing the therapeutic potential of the technique.…”
Section: Nt Efficiencymentioning
confidence: 99%
“…The donor cells could be classified as either: (1) blastomeres from the early embryo, (2) embryonic stem cells (ES), (3) somatic stem cells or (4) fully differentiated somatic cells. The use of blastomeres as donor cells were successfully used to generate the first mammalian clones, [1][2][3] Embryonic stem cells have been successfully used as donor cells in the mouse. 4,5 Higher rates of development have been reported when using ES cells as the donor cells compared to somatic donor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the transplanted nucleus undergoes extensive morphological changes such as nuclear swelling, dispersal of nucleoli, nuclear envelope breakdown, and premature chromosome condensation. These observations were made following transfer of embryonic (Stice and Robl 1988;Prather et al 1989;Collas and Robl 1991;Kanka et al 1991) as well as somatic (Czolowska et al 1984) nuclei. Global changes in transcriptional activity of the transplanted nuclei have also been observed Schultz et al 1996;Smith et al 1996;Lavoir et al 1997).…”
mentioning
confidence: 99%